Discriminating Models of Different Sized Color Geometric Figures - Y A Chudina (Peoples' Friendship University of Russia (RUDN University), 2013)
The data obtained by us in two experiments, where the different sized color geometric figures were used as stimuli, are described in the article. We have built configurative and categorical discriminating models differing by formal and intensional characteristics. The models reflect the different ways of visual gestalt generation: additive and non-additive principles of consolidation of neural mechanisms analyzing the visual features of the picture.